Multiple Myeloma Associated with HIV Infection in a Transgender Woman: Case Report and Review of an Integrated Management Approach - Arequipa, Tomás Andrés Lasso; Pullupaxi, Erika Daniela Criollo; Montenegro, Camila Sinaí Yánez; Maila, Elian Andrés Urvina; Samaniego, Kimberly Camila Lastra; Contento, Joselyn Carolina Piarpuezan; Betancourt, Carlos Andrés Vallejo (Brazilian Journal of Case Reports, 2026)
Multiple myeloma (MM) is a malignant hematologic neoplasm characterized by the clonal proliferation of plasma cells within the bone marrow, associated with the production of monoclonal immunoglobulins that lead to progressive bone destruction. This condition typically manifests with hypercalcemia, renal insufficiency, anemia, and lytic bone lesions, which constitute the CRAB criteria used for diagnosis. MM accounts for approximately 10% of hematopoietic neoplasms and about 1% of all cancers worldwide. The median age at diagnosis ranges from 65 to 70 years, and the disease is rare in individuals younger than 40 years. Established risk factors for MM include advanced age (predominantly affecting individuals over 65 years), male sex, African descent, obesity, the presence of monoclonal gammopathy of undetermined significance (MGUS), and certain precursor plasma cell disorders. MGUS is the most common precursor condition, with an estimated annual progression rate of approximately 1% to active multiple myeloma. Beyond classical risk factors, chronic states of immunosuppression, such as human immunodeficiency virus (HIV) infection, have been associated with humoral immune dysfunction and the development of plasma cell disorders. Epidemiological studies and case series suggest that patients living with HIV have an increased risk of developing monoclonal plasma cell disorders, including MGUS and MM, with some reports documenting a 2- to 5-fold higher risk compared with the general population. Clinical presentation in these patients also appears to occur at younger ages and with atypical features, posing an additional diagnostic challenge. This case highlights the importance of early diagnosis and comprehensive management in patients with HIV/AIDS, particularly those with poor adherence to antiretroviral therapy, who may be more susceptible to developing malignant hematologic conditions such as MM.